Calcium phosphate nanoparticles for potential application as enamel remineralising agent tested on hydroxyapatite discs. Issue 47 (26th November 2021) - Mok, Zi Hong; Mylonas, Petros; Austin, Rupert; Proctor, Gordon; Pitts, Nigel; Thanou, Maya
Abstract : Calcium phosphate nanoparticles (hydroxyapatite, 63.9 ± 15.9 nm, rod-shaped, Ca/P: 1.39, low crystallinity, calcium-deficient, carbonated) were shown to increase the surface microhardness and step height of eroded hydroxyapatite discs. Abstract : Calcium phosphate exhibits excellent biocompatibility, and with particle size in the nanoscale, calcium phosphate nanoparticles (CPNPs) were explored to replace the hydroxyapatite lost in the nanoporous teeth due to dental erosion. CPNPs (2% w/v) colloidally stabilised by sodium citrate were synthesised via co-precipitation. They were characterised in terms of particle size, morphology, crystallinity, Ca/P ratio and calcium ion release. To ensure uniformity of the substrate, hydroxyapatite (HA) discs were examined as an alternative substrate model to enamel. They were eroded in acetate buffer (0.5 M; pH 4.0) at various timepoints (1, 5, 10, 30 min, and 2, 4 h), and their physical differences compared to enamel were assessed in terms of surface microhardness, surface roughness and step height. The remineralisation properties of the synthesised CPNPs on eroded HA discs at different pH levels were investigated. It was established that CPNPs were heterogeneously deposited on the HA discs at pH 9.2, whereas newly precipitated minerals from CPNPs were potentially formed at pH 6.2.